2023
DOI: 10.3390/en16052363
|View full text |Cite
|
Sign up to set email alerts
|

Investment and Innovation Activity of Renewable Energy Sources in the Electric Power Industry in the South-Eastern Region of Ukraine

Abstract: Nowadays, the Ukrainian electricity industry is experiencing difficult conditions, as it is operating in a mode of depletion of its production potential. At the same time, the transition to sustainable and renewable energy is the necessary basis for the country’s welfare and for ensuring its energy security. Therefore, today we cannot do without the additional attraction of sources of funding from investors. The purpose of the survey is to study the pattern and effectiveness of investments and identify links a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Many research papers are dedicated to RE development, including investment issues [18][19][20][21][22], the identification of drivers and barriers for the effective deployment of RE facilities [23][24][25], the evaluation of economic, environmental, social, and other benefits from RE project implementation, etc. [26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many research papers are dedicated to RE development, including investment issues [18][19][20][21][22], the identification of drivers and barriers for the effective deployment of RE facilities [23][24][25], the evaluation of economic, environmental, social, and other benefits from RE project implementation, etc. [26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In turn, Steffen and Patt (2022) examined how the Russian-Ukrainian war changes public support for clean energy policy. Sala et al (2023) examined the effectiveness of investments in renewable energy sources. The authors identified the relationships between key technical and economic parameters and these investments, on the example of wind power plants located in the south-eastern part of Ukraine.…”
Section: The Article Bymentioning
confidence: 99%
“…A higher market share generally indicates a more competitive position. [5,7,8]. It is necessary to note, that Ukraine has significant renewable energy potential, particularly in solar, wind, and biomass resources.…”
Section: Introductionmentioning
confidence: 99%
“…The South-Eastern region is known for its favorable conditions for solar and wind energy production. [8,9]. However, withdrawal the fossil power generating sources is impossible [10,11].…”
Section: Introductionmentioning
confidence: 99%